Enzymatic Activity in the Anaerobic Co-Digestion of Cavitated Coffee Waste and Sewage Sludge - Elżbieta Wołejko; Urszula Wydro; Aleksandra Szaja; Agnieszka Montusiewicz; Magdalena Lebiocka (Energies)
Hydrodynamic cavitation (HDC) as a pre-treatment method is innovative and has potential for wide-scale industrial applications. The novelty of this research involves evaluating the enzymatic activity in the anaerobic co-digestion (AcD) of hydrodynamically cavitated coffee waste (CW) and municipal sewage sludge (SS) as well as its influence on the AcD performance. The effectiveness of AcD was assessed on the basis of changes in the physico-chemical composition of the feedstock and digestate as well as the biogas/methane yield, and attention was paid to the effect of coffee waste on enzyme activity, including that of β-Glucosidases (β-Glu), protease (PR), urease (URE), phosphomonoesterases acid (ACP) and alkaline (ALP). Moreover, the changes in the heavy metal content after the AcD of CW and SS were investigated. Comparing the enzymatic activity of the feedstock and digestate, we observed that the URE, ACP and ALP activities were 4.5 to 11 times higher for the feedstock than the enzyme activities in the digestate. Moreover, when using CW cavitated for 30 min, the highest enzymatic activity in both the feedstock and digestate occurred. The results indicated that the relationship between the β-Glu activity and biogas yield showed the strongest positive correlation (r = 0.98 at p ≤ 0.05). At the same time, a positive correlation between the PAC, PAL, URE and PR activity and methane yield and methane content at p ≤ 0.05 was observed. The obtained results allow us to conclude that, in the future, such a digestate could be used as a bio-fertilizer to improve degraded soil to activate microbial populations.